2020
DOI: 10.5530/pj.2020.12.168
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum sanctum: Role in Diseases Management Through Modulating Various Biological Activity

Abstract: Tulsi has been found to be a chief source of many biologically active compounds like Ursolic acid, Eugenol, Rosmarinic acid, Linalool, Carvacrol, and ABSTRACT Medicinal plants are used commonly by traditional medical practitioners in their daily practice for the treatment of various diseases. The treatment based on natural products are preferred because they are more economic and have lesser side-effects. In this regards, Ocimum sanctum commonly known as holy basil or tulsi is used in the diseases cure and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(53 reference statements)
0
9
0
3
Order By: Relevance
“…Aqueous extract of the O. sanctum leaves may function simply by quenching the free radicals generated during oxidative stress or may improve the antioxidant enzyme status of the tissue in the face of the oxidative stress (Mitra et al, 2014). Tulsi has been found to be a chief source of many biologically active compounds like ursolic acid, eugenol, rosmarinic acid, linalool, carvacrol and β caryophyllene and these compounds play a significant role in the treatment and prevention of many diseases (Almatroodi, Alsahli, Almatroudi, & Rahmani, 2020). The antioxidant nature of O. sanctum leaf extract might have reduced the oxidative stress caused by NaF in D. melanogaster used in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Aqueous extract of the O. sanctum leaves may function simply by quenching the free radicals generated during oxidative stress or may improve the antioxidant enzyme status of the tissue in the face of the oxidative stress (Mitra et al, 2014). Tulsi has been found to be a chief source of many biologically active compounds like ursolic acid, eugenol, rosmarinic acid, linalool, carvacrol and β caryophyllene and these compounds play a significant role in the treatment and prevention of many diseases (Almatroodi, Alsahli, Almatroudi, & Rahmani, 2020). The antioxidant nature of O. sanctum leaf extract might have reduced the oxidative stress caused by NaF in D. melanogaster used in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Kemangi merupakan salah satu tanaman berkhasiat Indonesia yang banyak mengandung komponen metabolit sekunder aktif dan kegunaannya berkaitan erat dengan aktivitas seksual (Wicaksono et al, 2013). Kemangi juga diketahui memiliki khasiat sebagai antioksidan, antikanker, radioprotektif, antihipertensi dan kardioprotekrif, antimikroba, imunomodulator, hepatoprotektor, dan antifertilitas (Almatroodi et al, 2020;Ponnusam et al, 2015;Baruah & Kma, 2019). Kemangi memiliki aroma yang khas karena mengandung minyak atsiri (sineol, eugenol, linalool, timol), karvakrol, asam ursolat, asam askorbat, kampene, betakarotin, terpineol, aldehid, alkaloid, dan flavonoid (Vinnata et al, 2018;Verma, 2016).…”
Section: Pendahuluanunclassified
“…Penelitian Navin et al (2013 menunjukkan bahwa ekstrak minyak esensial kemangi dapat bertindak sebagai antibakteri dan antiinflamasi yang signifikan. Ekstrak metanol dan air dari kemangi dapat menghambat inflamasi akut yang ditimbulkan dari pemberian karagenan (Almatroodi et al, 2020). Ekstrak kemangi mengandung senyawa fenol yang berfungsi sebagai antioksidan dan mampu meningkatkan jumlah leukosit menurut El-Shafei et al, (2021).…”
Section: Pembahasanunclassified
“…Kelm et al [20] reported that compounds isolated from O. sanctum L. extract, Civsilineol, Civsimavatine, Isothymonin, Apigenin, Rosavinic acid and Eugenol were observed for their anti-inflammatory activity. A methanolic extract and an aqueous moratorium of O. sanctum L. reluctant acute as well as chronic inflammation in rats as tested by carrageenininduced pedal edema and craton oil -induced granuloma and exudates, respectively [21].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%